The Relationship Between Academic Self Efficacy And Study Time Of Undergraduate Nursing Students - Rasdiyanah, Rasdiyanah; Ilhamsyah, Ilhamsyah (Poltekkes Kemenkes Banjarmasin, 2024)
Students' behavior in certain situations is generally influenced by environmental and cognitive factors, especially cognitive factors related to academic self-efficacy that they are able or unable to perform satisfactory actions. Because of having academic self-efficacy in the learning process, students will be motivated to achieve better academic achievement. Academic self-efficacy is one of the physiological aspects that affects a student’s success because self-efficacy has an impact on students’ choices, problem solving, and persistence in achieving goals. This study is descriptive correlational approach, it investigated the relationship between academic self-efficacy and the study time of undergraduate nursing students. The results indicated that the students' self-efficacy is relatively high, the relationship between academic self-efficacy and the study time is not significant, which means that academic self-efficacy does not effect on the study time of students.